Surgical treatment of neovascular glaucoma : a systematic review and meta-analysis - Shchomak, Zakhar (2018)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2017